Shaping of Looped Miniaturized Chalcogenide Fiber Sensing Heads for Mid-Infrared Sensing - Patrick Houizot; Marie-Laure Anne; Catherine Boussard-Plédel; Olivier Loréal; Hugues Tariel; Jacques Lucas; Bruno Bureau (Sensors, 2014)
Chalcogenide glass fibers are promising photonic tools to develop Fiber Evanescent Wave Spectroscopy (FEWS) optical sensors working in the mid-infrared region. Numerous pioneering works have already been carried out showing their efficiency, especially for bio-medical applications. Nevertheless, this technology remains confined to academic studies at the laboratory scale because chalcogenide glass fibers are difficult to shape to produce reliable, sensitive and compact sensors. In this paper, a new method for designing and fabricating a compact and robust sensing head with a selenide glass fiber is described. Compact looped sensing heads with diameter equal to 2 mm were thus shaped. This represents an outstanding achievement considering the brittleness of such uncoated fibers. FEWS experiments were implemented using alcoholic solutions as target samples showing that the sensitivity is higher than with the routinely used classical fiber. It is also shown that the best compromise in term of sensitivity is to fabricate a sensing head including two full loops. From a mechanical point of view, the breaking loads of the loop shaped head are also much higher than with classical fiber. Finally, this achievement paves the way for the use of mid-infrared technology during in situ and even in vivo medical operations. Indeed, is is now possible to slide a chalcogenide glass fiber in the operating channel of a standard 2.8 mm diameter catheter.